22 gallons is 83.279 liters
Y = 3x + b
6 = 3(4) + b
6 = 12 + b, b = -6
Equation: y = 3x - 6
4(x - 2) + 6 = 2(5x - 6) <em>use distributive property</em>
(4)(x) + (4)(-2) + 6 = (2)(5x) + (2)(-6)
4x - 8 + 6 = 10x - 12
4x - 2 = 10x - 12 <em>add 2 to both sides</em>
4x = 10x - 10 <em>subtract 10 from both sides</em>
-6x = -10 <em>divide both sides by (-6)</em>
x = 10/6
<h3>x = 5/3</h3>
Answer:
If you look at the "Standard Form" column, you can take any number from an upper row and divide it by 4 to get the number in the row below it.
For example: You can take 256 and divide it by 4, and that will give you 64. Like wise, if you take 64 and divide it by 4 you will get 16.
This tells us that every time you add 4 to the equation, your answer will keep increasing 4 times.
Step-by-step explanation:
Hope that makes sense :)
If you still don't get it, please let me know.
9^-2 = 1/81 or 0.0123
When there is a negative in front of the exponent it makes a fraction. It is usually just 1/the number it equals if it were positive.